The Relationship of Emotional Intelligence Elements and Effective Leadership of Master Degree Students: A Case of AU MIT Myanmar University - Phoo Aung, May Zun; Fernando, Maria Socorro C.L. (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
Emotional intelligence is an important topic in every industry as a tool to measure leadership competencies. Leaders with high emotional intelligence can build a successful team by inspiring and motivating team members to achieve their goals. Many organizations are in demand of highly emotionally intelligent leaders for a competitive and challenging today`s world and training future leaders with high emotional intelligence becomes an important matter for academic institutes. Therefore, this research intended to investigate the relationship between emotional intelligence elements: self-awareness, self-regulation, motivation, empathy and social skills, and effective leadership of master’s students from AU MIT Myanmar University. Mixed method research was conducted in this study. Quantitative data was gathered from 39 master’s students as a sample of this study using a questionnaire, and qualitative data was gathered from interviews with six students. The quantitative data from the Pearson correlation test shows that all emotional intelligence elements correlate with effective leadership. The results of qualitative data by content analysis show that effective leaders are leaders who can know their feelings, and others, and interact or behave by recognizing and managing emotions well and being supportive of others. Finally, strategies for enhancing the emotional intelligence of students from AU MIT Myanmar University will be proposed based on the findings of all results.